Synergistic Effect of Core/Shell-Structured Composite Fibers: Efficient Recovery of Rare-Earth Elements from Spent NdFeB Permanent Magnets - Jung, Youngkyun; Lee, Yun; Yoon, Su-Jin; Choi, Jae-Woo (Springer Nature, 2024)
NdFeB magnets are third-generation permanent magnets that are employed as indispensable components in various industries. Notably, rare-earth elements (REEs) such as Dy and Nd must be efficiently recovered from end-of-life magnets to enable resource circulation and reinforce unstable supply chains. To that end, this paper reports synergistically performing core/shell-structured composite fibers (CSCFs) containing sodium polyacrylate and nanoporous zeolitic imidazolate framework-8 (NPZIF-8) nanocrystals as a readily recoverable adsorbent with an exceptional REE-adsorbing ability. The CSCF core forms an NPZIF-8 nanocrystal shell on the fiber surface as well as draws REEs using its dense sodium carboxylate groups into the NPZIF-8 nanocrystal lattice with high specific surface area. The CSCFs exhibit significantly higher maximum adsorption capacities (468.60 and 435.13 mg·g−1) and kinetic rate constants (2.02 and 1.92 min−1) for the Nd3+ and Dy3+ REEs than those of previously reported REE adsorbents. Additionally, the simple application of the CSCFs to an adsorption reactor considerably mitigates the adsorbent-shape-induced pressure drop, thereby directly influencing the energy efficiency of the recovery. Moreover, the high REE-recovery ability, tractability, and recyclability of the CSCFs offers a pragmatic pathway to achieving cost-effective REE recovery. Overall, this study provides new insights into designing synergistically performing core/shell architectures for feasible REE recovery.